Evaluation of halal assurance system on instant seasoning products cv. x, semarang - Rifqi, Muhammad; Khairi, Amalya Nurul (Journal of Halal Science and Research, 2021)
Instant seasoning is a mixture of spices with a certain composition that is usually used as a cooking spice. The process of making instant seasoning has a critical point of halal in its manufacture because it can be exposed to unclean contamination during production process. Purpose of this study was to analysis the suitability of the application of halal assurance system based in HAS 23000 in CV. X. Method used in data collevtion is through observation, interviews, and study literature. Results obtained after a through analysis is that not all materials used have received halal approval by LPPOM MUI because mushroom broth does not find data regarding certificate number which indicates that validity period has passed and there are deficiencies in criteria for halal assurance system from material, tarining and education, written procedures for critical activities, internal audit, and management review.